2021
DOI: 10.1029/2021gl095003
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Global Hybrid Simulations of High Latitude Magnetopause Reconnection and Flux Ropes During the Northward IMF

Abstract: High latitude magnetopause reconnection with different northward IMF clock angles is studied by using 3-D global hybrid simulations • High latitude magnetopause flux ropes (HLMFRs) with four topologies of magnetic field lines are formed by multiple X-line reconnection • IMF clock angle effects where the HLMFRs occurs and the direction of the HLMFRs' axis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…These FTEs may coalesce with each other because of their different propagating speeds, and new FTEs are generated at the magnetopause near Mercury. The coalescence of FTEs is a re-reconnection process, which has also been well simulated and studied by performing 3D global hybrid simulations at the Earth's magnetopause (Guo et al 2021a(Guo et al , 2021b(Guo et al , 2021c and ubiquitously observed in planetary magnetospheres (Wang et al 2017;Zhou et al 2017;Zhong et al 2020). At t = 135.72 s, F2 and F3 have merged into one FTE "F2,3," and a new FTE "F4" appears at about x = −0.5R M .…”
Section: Simulation Resultsmentioning
confidence: 96%
“…These FTEs may coalesce with each other because of their different propagating speeds, and new FTEs are generated at the magnetopause near Mercury. The coalescence of FTEs is a re-reconnection process, which has also been well simulated and studied by performing 3D global hybrid simulations at the Earth's magnetopause (Guo et al 2021a(Guo et al , 2021b(Guo et al , 2021c and ubiquitously observed in planetary magnetospheres (Wang et al 2017;Zhou et al 2017;Zhong et al 2020). At t = 135.72 s, F2 and F3 have merged into one FTE "F2,3," and a new FTE "F4" appears at about x = −0.5R M .…”
Section: Simulation Resultsmentioning
confidence: 96%
“…Based on the above simulation results, Figures 5c and 5d summarize how the IMF By ${B}_{y}$ controls the azimuthal motion of PMAFs. With By<0 ${B}_{y}< 0$, the X‐line of magnetopause reconnection tilts, unparallel to the equatorial plane (Guo et al., 2021a, 2021b, 2021c). Thus, the reconnection outflows (blue arrows in Figure 5c) from the tilted X‐line are dawnward and poleward in the southern hemisphere, and they push the magnetopause flux ropes dawnward and poleward.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 4a, the flux ropes “1–7” with parallel temperature enhancements are formed by multiple X‐line reconnection in the noon‐midnight meridian plane (Guo et al., 2021b, 2021c; Lee & Fu, 1985; Lee et al., 1993; Tan et al., 2011). These flux ropes are formed at low latitudes and then move to higher latitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid codes have been used for modeling large systems such as (small or artificially reduced) planetary magnetospheres. However such large scale models typically poorly resolve the Hall scale [5,6,7,8]. Not resolving such sub-ion scale current sheets may result in errors leading to spurious macroscopic behavior [9].…”
Section: Introductionmentioning
confidence: 99%